PENGARUH IKLAN LAYANAN MASYARAKAT TERHADAP SIKAP DENGAN DISONANSI KOGNITIF SEBAGAI PEMODERASI - Uswatun Chasanah; Muhamad Mathori (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This study analyzes the effect of public service ads on the attitudes of students with cognitive dissonance (Cognitive Dissonance) as moderating in the city of Yogyakarta. This study took a sample of students in the city of Yogyakarta from Diploma to S3. Samples were distributed to 250 respondents, but only 223 were processed. The sampling method using a non-probability sampling approach was purposive sampling. Before the data analysis is performed first, the validity and reliability test is performed, in the validity test two approaches are used, namely using Pearson’s Coefficient Correlation and Confirmatory Factor Analysis (CFA). ILM3 and CD1 are invalid, the rest are valid, while the validity with CFA found three invalid statement items namely ILM2, CD1, CD2 and the rest are all valid. ILM reliability tests are all reliable above 0.6. This study uses multiple regression analysis with the help of the SPSS series 23 program, the results of multiple regression shows there is an influence of Public Service Advertising (PSA) on Student Attitudes (SK), while Cognitive Dissonance does not significantly affect the relationship between Public Service Adverts and Student Attitudes. For hypothesis testing only the first hypothesis is proven, the other hypotheses are not proven.